Teachers' Strategies In Developing Students' Critical Thinking And Critical Reading: Strategi Guru Dalam Meningkatkan Kemampuan Membaca Kritis Dan Berpikir Kritis Siswa - Hakim, Lystiana Nurhayat; Rachmawati, Etika; Purwaningsih, Sundari (Pedagogia : Jurnal Pendidikan, 2021)
Critical thinking in the education of Indonesia has not been well socialized; students also tend to accept information without evaluating it first and change ideas uncritically. This case is very detrimental. Therefore, teacher plays an important role in developing stu- dents' critical thinking and critical reading ability. The puropse of this study is to find out teachers' strategies in improving students' critical thinking and critical reading ability. This study used qualitative research design, interview and questionaire was used asa research instruments in this study. The results of this study shows strategies used by the teacher are asking open-ended questions, restate and clarify the meaning of a few sentences from the text, and use small group discussions with specific tasks assigned. In short, the teachers' understanding of critical reading and critical thinking is low, their strategy in improving students' critical reading is also limited.